Can Internal Mechanisms Control Detect Corruption Through Fraudulent Behaviour? - Magda Siahaan; Theonino David Nauli; Bonar Paul Siahaan (AFRE (Accounting and Financial Review), 2024)
This paper aims to find the link between integrated GRC (governance, risk management, and compliance) and internal audit, which is included in internal mechanisms control for detecting corruption and regulatory compliance in its success. This study uses the Partial Least Square method for primary data analysis on 48 public and private companies and hypothesis testing, supplemented by interviews with respondents.Â  This study indicates the significant influence of the integrated GRC on corruption detection and necessary mediation with internal audit, in addition to the importance of regulatory compliance and the need for the regulatory drive for the successful implementation of internal mechanisms control. The limited application of GRC for model alignment, strategic integration, and standardization of GRC terminology shows the depth of context to identify the application of GRC in organizations in their success in detecting corruption. Organizations can assess root causes or weaknesses in existing systems/strategies/ regulations in detecting corruption to eradicate corruption. It is still rare for integrated GRC research to mediate the relationship between internal audit and corruption detection and its relation to regulatory compliance.DOI: https://doi.org/10.26905/afr.v7i1.11893